The effect of mean annual temperature on the incidence of distal radial fractures. (November 2018) - Johnson, Nick A.; Stirling, Euan; Dias, Joseph J.
We investigated the relationship between the incidence of distal radial fractures and mean annual temperature. Data for all adult patients presenting to our unit with a distal radial fracture from 2007–2014 were analysed. Incidence rates were compared with meteorological records. A Poisson regression model was used to analyse trends. Distal radial fractures were sustained by 8831 adults. The only significant change in fracture incidence occurred in 2010, in women only. This was the coldest year in the United Kingdom for over 20 years. Analysis by age bands during 2010 showed fracture incidences were significantly higher for women aged 40–69 with a higher percentage of injuries occurring in the street. These women are likely to remain mobile during bad weather but frequently have underlying osteoporosis. Falls prevention programmes should address this group with specific strategies. Simple measures, such as walking aids, appropriate footwear and avoidance of non-essential travel in slippery conditions, may reduce risk. Level of evidence: IV